Analisis Komparatif Penerapan Strategi Pembelajaran Inovatif Dalam Meningkatkan Keaktifan, Kreativitas, Motivasi Belajar, Pengelolaan Kecemasan, Dan Keterampilan Passing Bawah Siswa Di SMA - Naziva Putri Permatasari; Aulia Iffa Safitri; Imam Anugrah; Dewi Wulanndari; Alya Wulanndari; Muhamad Rizqi; Ayu Ernawati; Farizal Imansyah (Tirai Edukasi : Jurnal Pendidikan, 2026)
This study analyzes the implementation of seven innovative learning strategies during the School Field Introduction Program (PLP) at SMA PGRI 1 Palembang (March-May 2026): (1) Think-Pair-Share (TPS) model in simple songwriting for Grade X (Naziva Putri Permatasari), (2) melodica-based learning on the national anthem Garuda Pancasila for Grade XI (Aulia Iffa Safitri), (3) Quizizz media to enhance engagement in Healthy Living Activities in PJOK for Grade XI (Imam Anugrah), (4) short-distance running to improve PJOK motivation in Grade X (Dewi Wulanndari), (5) management of emotional influence on backward roll anxiety in Grade X (Alya), (6) deep learning-based PJOK on handball, athletics, softball, and floor gymnastics in Grade X (Muhamad Rizqi), and (7) cooperative learning strategies to improve volleyball underhand passing in Grade X (Ayu Ernawati). A qualitative descriptive method was applied through observation, teaching assistance, and independent practice. Results indicate all seven strategies effectively enhanced student engagement, creativity, motivation, and self-confidence. The cooperative learning approach proved effective in improving volleyball underhand passing skills and fostering collaboration through heterogeneous small-group models.